Endleleni: Political activism of Winnie Madikizela-Mandela as pastoral caregiving - Penxa Matholeni, Nobuntu (Stellenbosch theological journal, 2022)
Winnie Madikizela-Mandela is one of the most contentious figures in South African history. Some viewed the ex-wife of President Mandela affectionately as the "mother of the nation" for her leadership during the apartheid era, and for her work in the townships of Soweto. Others viewed her as a villain connected to the controversial death of 14-year-old Stompie Seipei Moeketsi. Scholars write about her role as an activist, usually from the perspective of her social work career. This article seeks to adopt a totally different stance, where the focus shifts to her life as an activist mother, particularly in relation to caregiving. It uses a pastoral theological lens in combination with the endleleni metaphor. The latter, which is the amaXhosa metaphor meaning "on the road", will be explored in more detail in the article. The indigenous storytelling methodology will be employed using the lived experiences of Nomzamo Madikizela-Mandela and my own story to answer the question: "Considering the metaphor of endleleni, to what extent is the role of Winnie Madikizela-Mandela as an activist mother an attribute of pastoral caregiving?" It is noteworthy to mention that a strong communal sense has an influence on the telling and writing of stories in black communities. If one comes from a background where the individual is inherently part of the communal, that perspective will affect how one tells the story.